CRISPR/Cas9: A Tool to Circumscribe Cotton Leaf Curl Disease - Iqbal, Zafar; Sattar, Muhammad N.; Shafiq, Muhammad (Frontiers in Plant Science, 2016)
The begomoviruses (family Geminiviridae) associated with cotton leaf curl disease (CLCuD) pose a major threat to cotton productivity in South-East Asia including Pakistan and India. These viruses have single-stranded, circular DNA genome, of ~2800 nt in size, encapsidated in twinned icosa-hedera, transmitted by ubiquitous whitefly and are associated with satellite molecules referred to as alpha- and betasatellite. To circumvent the proliferation of these viruses numerous techniques, ranging from conventional breeding to molecular approaches have been applied. Such devised strategies worked perfectly well for a short time period and then viruses relapse due to various reasons including multiple infections, where related viruses synergistically interact with each other, virus proliferation and evolution. Another shortcoming is, until now, that all molecular biology approaches are devised to control only helper begomoviruses but not to control associated satellites. Despite the fact that satellites could add various functions to helper begomoviruses, they remain ignored. Such conditions necessitate a very comprehensive technique that can offer best controlling strategy not only against helper begomoviruses but also their associated DNA-satellites. In the current scenario clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR associated nuclease 9 (Cas9) has proved to be versatile technique that has very recently been deployed successfully to control different geminiviruses. The CRISPR/Cas9 system has been proved to be a comprehensive technique to control different geminiviruses however, like previously used techniques, only a single virus is targeted and hitherto it has not been deployed to control begomovirus complexes associated with DNA-satellites. Here in this article, we proposed an inimitable, unique and broad spectrum controlling method based on multiplexed CRISPR/Cas9 system where a cassette of sgRNA is designed to target not only the whole CLCuD-associated begomovirus complex but also the associated satellite molecules.